Ex Ante Economic Analysis in AKIS Projects : Methods and Guidelines for Good Practice - Horstkotte-Wesseler, Gesa; Maredia, Mywish; Byerlee, Derek; Alex, Gary (World Bank, Washington, DC, 2013)
This note outlines an approach to economic analysis in agricultural research and extension (R&E) projects financed under World Bank loans and credits. It provides guidelines and recommends steps to take during project preparation and implementation. 1) agricultural research investments should be evaluated at the level of research programs for important commodities or production systems. 2) agricultural extension investments are often best evaluated using rough measures of cost-effectiveness or unit costs. 3) alternatively, break-even analyses can be conducted for extension programs to show the minimum impact needed to justify proposed expenditures. 4) during project preparation, economic analyzes should focus on retrospective technology adoption and impact studies, and prospective technology case studies . 5) during project implementation, the emphasis should be on establishing systems that incorporate economic analysis on an ongoing basis into R&E evaluation, planning, and priority setting. 6) evaluators within the national agricultural research system should conduct the economic analyzes whenever possible to build local capacity and foster local ownership of the results. 7) all economic analyzes should use the economic surplus method or a simplification thereof, such as a cost-benefit analysis.